2015
DOI: 10.1021/acs.energyfuels.5b01291
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Condensable Hydrocarbons in a Dual Fluidized Bed Biomass Gasifier

Abstract: Biomass gasification is a primary process in the thermochemical conversion of biomass into biofuels, chemicals, and electricity. The produced raw gas consists of permanent gas species, such as hydrogen (H 2 ) and carbon monoxide (CO), with variable amounts of heavier/larger species, depending on the gasification technique and process conditions employed. These heavier species are often referred to as tar, which is herein defined as all species with boiling points that lie between the boiling points of benzene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
62
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(68 citation statements)
references
References 25 publications
(77 reference statements)
6
62
0
Order By: Relevance
“…For the olivine case after 1 week of operation, the total elemental yields of CHO in the hot dry gas were instead estimated by means of the permanent gas and the SPA-tar yields. This calculation underestimates the carbon conversion and oxygen transport due to the existence of undetectable condensable species [38], which are not accounted for.…”
Section: Gas Measurementsmentioning
confidence: 99%
See 3 more Smart Citations
“…For the olivine case after 1 week of operation, the total elemental yields of CHO in the hot dry gas were instead estimated by means of the permanent gas and the SPA-tar yields. This calculation underestimates the carbon conversion and oxygen transport due to the existence of undetectable condensable species [38], which are not accounted for.…”
Section: Gas Measurementsmentioning
confidence: 99%
“…In the case of quartz-sand, 363 the alkali species are most likely chemically bound to silicon, which cannot be desorbed with steam 364 [26]. Therefore, the trend in the quartz-sand case shown in Fig.11 is in line with the shorter residence 365 time of the fuel in the gasifier as fluidization velocity increases [38]. When alkali species are physically 366 bound to the material, as in the case of bauxite [20], a greater steam flow results in enhanced char 367 conversion, in line with the enhanced desorption of alkali species from the material.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…Benzene can be formed through the dealkylation of alkyl-aromatics [32,36] and the dehydroxylation of phenol [35,38]. However, Israelsson et al [45,49] have reported that at temperatures <830°C, the conversion reactions of toluene and phenol are not sufficient to explain the high yields of benzene obtained with an increase in process temperature. Similarly,…”
Section: Sources Of Minor Hydrocarbons In Biomass Gasification the Pmentioning
confidence: 99%